Distinct sociodemographic differences in incidence and survival rates for human papillomavirus (HPV)-like, non-HPV-like, and “other”-like oral cavity and pharynx cancers: An analysis of Surveillance, Epidemiology and End Results (SEER) Program data - Jordan, Kelsey H.; Fisher, James L.; Paskett, Electra D. (Frontiers in Oncology, 2022)
Purpose: Oral cavity and pharynx cancer (OCPC) cases are traditionally dichotomized into human papillomavirus (HPV) and non-HPV types. Using a proxy for HPV status, the objective was to evaluate differences in incidence and survival rates of OCPC anatomic sub-sites identified as: 1) HPV-like; 2) non-HPV-like (i.e., tobacco/alcohol-related); and 3) “other”-like (i.e., not predominantly HPV-like nor tobacco/alcohol-like) OCPCs. Methods: Data from the Surveillance, Epidemiology and End Results Program were used to examine incidence and survival rates for OCPC categories over time and according to age, sex, race, ethnicity, stage at diagnosis, neighborhood socioeconomic status (i.e., nSES or Yost Index), and rurality/urbanity (i.e., Rural Urban Commuting Area (RUCA) codes). Although HPV status was unavailable in this dataset, OCPC anatomies and histologies were classified into three sub-categories, based on potential risk factors. Frequencies, average annual, age-adjusted incidence rates, five-year relative survival rates, and 95% confidence intervals were examined across and within OCPC categories. Results: HPV-like OCPC incidence rates sharply increased from 1975 through 2015 while non-HPV-like and “other”-like OCPC rates decreased, all converging to similar rates from 2016 through 2018. Increasing over time for both categories, survival was highest for HPV-like and lowest for non-HPV-like OCPCs; survival for “other”-like OCPCs remained stable. Generally, across OCPC categories, incidence and survival rates were significantly higher among males vs. females, Whites vs. African Americans, and non-Hispanics vs. Hispanics. “Other”-like OCPC incidence decreased with increasing nSES tertiles, while no nSES differences were observed for HPV-like and non-HPV-like OCPCs. Incidence rates were significantly lower among urban (vs. rural) residents. For all OCPC categories, survival rates were significantly higher with increasing nSES and variable across RUCA categories. Conclusion/Impact: HPV-like and non-HPV-like OCPC cases had distinct sociodemographic differences; “other”-like OCPC cases were a sociodemographic blend of HPV-like and non-HPV-like OCPC cases, resembling the sociodemographic makeup of non-HPV-like OCPC cases. To prevent new OCPCs, additional studies are needed to epidemiologically and clinically differentiate between OCPC categories so that high-risk groups can be better targeted in future public health interventions.